Pemberdayaan Kewirausahaan Generasi Muda Melalui Pembangunan Usaha Rintisan di Kabupaten Sukoharjo: Inisiasi Kegiatan Workshop di SMK PGRI Sukoharjo - Sudalyo, Ramadhian Agus Triono; Prasetyaningrum, Nurita Elfani; Nugrohotomo, Gesang Kristianto (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
In the era of globalization and technological advancements, young generations face increasingly complex economic challenges. Entrepreneurial skills have become essential to prepare them for a competitive future while also contributing to local economic development. This community service program aims to enhance entrepreneurial empowerment among the youth in Sukoharjo Regency through the development of start-up businesses. One of the initiatives undertaken is organizing a workshop at SMK PGRI Sukoharjo, attended by 21 twelfth-grade students. The training covers various aspects of entrepreneurship, including digital marketing, branding, product and service innovation, financial management, as well as legal and regulatory aspects of starting a business. This workshop involves three speakers from the Community Service Team of Universitas Surakarta, delivering comprehensive materials. Evaluation results show that 85% of participants found the materials provided highly relevant and beneficial for starting a business, and 90% of participants expressed readiness to apply the knowledge gained in independent business planning. The workshop also successfully increased participants' motivation to become entrepreneurs. Collaboration between universities and secondary education institutions provides students with access to knowledge and resources not readily available within the school environment. This initiative is projected to encourage participants to take concrete steps post-training, such as planning and developing start-up business ideas independently, and contributing to local economic development.